Oxypropylation of lignins and characterization of the ensuing polyols - Cateto, C.A. (2010)
Four lignin samples (Alcell, Indulin AT, Curan 27-11P and Sarkanda) were converted into liquid polyols by a chain extension reaction with propylene oxide (oxypropylation). The reaction was carried out in a batch reactor using potassium hydroxide (KOH) as a catalyst. The oxypropylation process was first optimized with Alcell lignin by modifying the lignin/propylene oxide ratio (L/PO, w/v) and catalyst content (C/(C+L), % w/w). L/PO ratios of 10/90, 20/80, 30/70 and 40/60, and catalyst contents from 2 to 5% were used. Based on the studied formulations, and considering the polyol requirements for polyurethane foam synthesis (a hydroxyl number (IOH) between 300 and 800 and a viscosity below 300 Pa.s), three formulations were chosen and applied for the oxypropylation the other lignin samples: 20/80/5, 30/70/2 and 35/65/2. The produced polyols were characterized. Their IOH and viscosity were found to be in the range of those typical of commercial polyols employed in polyurethane preparation.